Comparison of nerve graft and artificial conduits for bridging nerve defects - Mahmood Merican, A.; Ahmad, T.S. (Malaysian Medical Association, 2004)
A study of nerve regeneration through a 1cm defect in the peroneal component of the sciatic nerve was performed on sixteen rabbits. Either silicone or polytetrafluoroethylene (PTFE) tubes or nerve graft were used to bridge the defect and the opposite limb was not operated upon. The rabbits that underwent nerve grafting had favourable findings. In the PTFE group, a nerve-like structure was seen at the former gap site and histology confirmed viable axons within the tubes and distal to the repair site. In the silicone tube group, there were no myelinated axons demonstrated. The axonal count for the grafted nerves and the nerves repaired with PTFE tube are on average 80.4% and 38.2% of that of the unoperated nerve, respectively. On average, the percentage anterior compartment muscle weight (expressed as a percentage of the unoperated limb) for the silicone, PTFE and nerve graft groups are 42.3%, 42.1%, and 72.7% respectively. The results show that although, PTFE conduits can bridge a nerve defect of 1cm, nerve grafting provides a superior and more predictable outcome.